Comparative Analysis of Unit Cost and Tariff of Ina CBG'S Orthopedic Patients with Implants at Wangaya Denpasar Hospital - I Nyoman Sunirda; Luh Putu Mahyuni (Eduvest - Journal of Universal Studies, 2026)
Orthopedic patients with implants represent a significant cost burden for hospitals due to the high price of implant devices. The shift in payment mechanism from Fee-for-Service to INA-CBG's creates financial challenges for hospitals, particularly when claim rates do not cover the actual cost of services. This study aims to analyze the comparison between unit costs calculated using the Activity-Based Costing (ABC) method and INA-CBG's rates for orthopedic patients with implants at Wangaya Hospital, Denpasar City. The study used a quantitative descriptive approach with a sample of 286 orthopedic patients with implants who were BPJS Kesehatan participants for the period January to December 2022. The results showed that the total unit cost based on ABC calculation was IDR 4,563,261,903, while the total INA-CBG's claims amounted to IDR 4,741,805,362, resulting in a surplus of IDR 178,543,459. However, of the 286 patients, 113 experienced a deficit with a total loss of IDR 838,204,192. Implants constituted the highest cost component, reaching 61.7% of the total unit cost. The study concluded that although hospitals earn an aggregate surplus, the inequality in outcomes across individual patients necessitates a comprehensive cost management strategy, including implant price negotiation and adherence to clinical pathways.